Effect of short-term aging on interfacial and mechanical properties of yttria stabilized zirconia (YSZ)/stainless steel joints. Issue 3 (March 2015) - Lin, Kun-Lin; Singh, Mrityunjay; Asthana, Rajiv
Abstract: Two types of Ag-based metallic interlayers, Ag–Cu–Pd and Ag–Cu–Ti, were used to join yttria-stabilized zirconia (YSZ) to stainless steel for solid oxide fuel cell (SOFC) applications. The joined samples were aged at 850 °C/100 h in air for evaluation of thermomechanical stability of the joints. The microstructure of the interlayers and the interfaces of YSZ/interlayers and steel/interlayers before and after aging were characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) equipped with energy dispersive spectrometer (EDS). The evaluation of tensile and shear strengths and hermeticity indicated that the joints with Ag–Cu–Ti interlayers have better bonding strength and hermeticity than the joints with Ag–Cu–Pd interlayers.